2019
DOI: 10.1021/acs.analchem.9b04711
|View full text |Cite
|
Sign up to set email alerts
|

Protein and Proteome Measurements with Microfluidic Chips

Abstract: Major scientific discoveries in the last two decades have been enabled by the development of high-throughput sequencing and mass spectrometry (MS) technologies. Omics analysis, at the genome, transcriptome, proteome, or metabolome levels, has paved the way for the elucidation of many molecular mechanisms that underlie disease, biomarker and drug-target discovery, and diagnostics and precision medicine applications. With the realization that the biological interpretation of results generated from biological tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 110 publications
(160 reference statements)
0
9
0
Order By: Relevance
“…Multichannel (cyclical) single molecule FISH (fluorescence in situ hybridization) techniques could be used for transcriptome level measurements while retaining the spatial resolution, which is key to correlate gene expression profile and local oxygen abundance. 157 Other approaches that have been developed for off-chip analyses include the determination of the cytokine secretion profile (secretomics) 158 and their metabolic activity using collected medium (metabolomics), 159 or their protein expression profile (proteomics), 160 as well as gene expression analysis or single-cell transcriptomic studies, notably single cell RNA sequencing, after recovery of the cellular materials. 161…”
Section: Oxygen Control In Microfluidic Devices: Our Vision For the F...mentioning
confidence: 99%
“…Multichannel (cyclical) single molecule FISH (fluorescence in situ hybridization) techniques could be used for transcriptome level measurements while retaining the spatial resolution, which is key to correlate gene expression profile and local oxygen abundance. 157 Other approaches that have been developed for off-chip analyses include the determination of the cytokine secretion profile (secretomics) 158 and their metabolic activity using collected medium (metabolomics), 159 or their protein expression profile (proteomics), 160 as well as gene expression analysis or single-cell transcriptomic studies, notably single cell RNA sequencing, after recovery of the cellular materials. 161…”
Section: Oxygen Control In Microfluidic Devices: Our Vision For the F...mentioning
confidence: 99%
“…Sonker et al [ 110 ] reported the possibility of using a specific separation system for integrated immunoaffinity extraction to study human serum matrix biomarkers in preterm infants. They used a reactive polymer to immobilize the antibody as a whole and selectively extracted targeted preterm infant markers.…”
Section: Applications Of Microfluidicsmentioning
confidence: 99%
“…It is expected that the specific cells in the biopsy sample will be treated individually. Further analysis should focus on system expansion, which obviously requires thorough optimization [ 110 ].…”
Section: Applications Of Microfluidicsmentioning
confidence: 99%
“…This advantage is useful to reduce invasiveness in liquid biopsy using blood, urine, saliva, and tears. Therefore, microfluidic devices have been applied as point-of-care (PoC) diagnostic devices [ 1 , 2 , 3 , 4 ]. Recently, an attractive PoC device has been developed [ 5 ] (i.e., a microfluidic device equipped with freeze-dried diagnostic reagents).…”
Section: Introductionmentioning
confidence: 99%